2015
DOI: 10.1007/s12011-015-0412-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Tripeptide Iron on Iron-Deficiency Anemia in Rats

Abstract: This study aims to investigate the effects of a tripeptide iron (REE-Fe) on iron-deficiency anemia rats. Sprague-Dawley rats were randomly divided into seven groups: a normal control group, an iron-deficiency control group, and iron-deficiency groups treated with ferrous sulfate (FeSO4), ferrous glycinate (Fe-Gly), or REE-Fe at low-, medium-, or high-dose groups. The rats in the iron-deficiency groups were fed on an iron-deficient diet to establish iron-deficiency anemia (IDA) model. After the model establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 37 publications
9
43
0
Order By: Relevance
“…Although many studies have shown that ferrous glycinate exhibits better bioavailability than ferrous sulfate152324, the mechanism of its high bioavailability is still unclear. In the present study, we found that gavage of SD rats with FeSO 4 or Fe-Gly did not affect their growth performance over a relatively short time period (two weeks), but that the SI level was significantly increased in the Fe-Gly-treated rats group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have shown that ferrous glycinate exhibits better bioavailability than ferrous sulfate152324, the mechanism of its high bioavailability is still unclear. In the present study, we found that gavage of SD rats with FeSO 4 or Fe-Gly did not affect their growth performance over a relatively short time period (two weeks), but that the SI level was significantly increased in the Fe-Gly-treated rats group.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that gavage of SD rats with FeSO 4 or Fe-Gly did not affect their growth performance over a relatively short time period (two weeks), but that the SI level was significantly increased in the Fe-Gly-treated rats group. SI is the amount of circulating iron that is bound to transferrin23, and it reflects iron absorption in the intestinal tract. These results are consistent with those of our previous study showing that Fe-Gly is absorbed better than FeSO 4 15.…”
Section: Discussionmentioning
confidence: 99%
“…For example, aspartame ( N - l -α-aspartyl- l -phenylalanine methyl ester) can interact with ferrous iron, and aspartame-ferrous iron complexes have been synthesized [10]. Fe-carbamyl glycine [20] and Arg-Glu-Glu-iron [18] have also been synthesized and studied as iron supplements.…”
Section: Iron-chelatable Protein Hydrolysatesmentioning
confidence: 99%
“…An iron ion can also be cargo. The tri-peptide Arg-Glu-Glu [18] was designed using the rules governing cell-penetrating peptides; the Arg residue improves the penetrability of the peptide and has been proven to promote iron absorption in the form of a chelate. Peptides produced by microorganisms have also been reported to contain iron or to have the ability to chelate iron.…”
Section: Iron-chelatable Protein Hydrolysatesmentioning
confidence: 99%
See 1 more Smart Citation